Deepfake and Media Ethics - Sorin Suciu (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages, 2024)
The advancement of artificial intelligence in a manner similar to the evolution of the living world through adaptation to the social environment and survival of the fittest algorithms has led to the emergence of species of programs that challenge the way media products are made and used. The very classical structure of mediated communication, and with it the perception of the public, is now altered by the interposition of generative software. An ecology of the products made with the help of these programs and an ethics that establish milestones on the road to technological advancement in public communication are evidently necessary.